A morphology optimization of enclosure shape of low melting point alloy-based PCM heat sink. (1st August 2023) - Huang, Pingrui; Wei, Gaosheng; Cui, Liu; Wang, Gang; Du, Xiaoze
Abstract: The enclosure shape of the phase change material (PCM) container is an important factor affecting the thermal performance of PCM heat sinks. A novel morphology optimization method is developed and used to optimize the enclosure shape of the low melting point alloy (LMPA) based PCM heat sink. The working process of the LMPA heat sink is firstly simulated with a simplified 2D numerical model. Then, morphology operations (erosion and dilation) are performed to update the material distribution in the design domain based on the simulation results. Through alternative execution of simulation and morphology operations, the desired optimal enclosure shape is obtained, and the optimization results are further experimentally validated. It is shown that the proposed optimization method can obtain better optimization results than traditional methods. With a fixed heat flux of 30 kW/m 2, the experimental temperature rise rate of the optimized LMPA heat sink is about 1.59 °C/min, which is 57.9 % lower than the theoretical minimum temperature rise rate of the corresponding rectangular LMPA heat sink. The experimental protection time of the optimized LMPA heat sink is about 924 s with a safety temperature of 120 °C, which is 31.3 % longer than the theoretical maximum protection time of the corresponding rectangular heat sink. Highlights: A morphology method is developed to optimize the enclosure shape of the PCM heat sink. The optimized results are compared with the rectangular PCM heat sink and experimentally validated. The temperature rising rate of the optimized PCM heat sink is lowered greatly. The managed time of the optimized PCM heat sink is prolonged effectively.